Analysis on the Artistic Features and Cultural Connotations of Folk Sachet in Northeast China (Journal of Global Arts Studies, 2024)
Background: The Northeast region of China, as the birthplace of the Chinese hunting and gathering civilization, has a long history and a unique culture. The folk sachets native to this area, as carriers of the local culture, bear rich regional cultural information. Objective: This study aims to analyze the shapes, patterns, and colors of Northeast Chinese folk sachets in connection with local culture, revealing the deeper cultural connotations embedded in these traditional handicrafts. Methods: Through literature review, field investigation of sachet artifacts, and interviews with artisans, this paper analyzes the sachets’ shapes, decorative patterns, and color schemes to interpret their cultural significance. Results: Northeast folk sachets exhibit a rich variety of forms, including open-mouth and closed-mouth types, as well as geometric, plant, and animal-shaped designs. Their patterns can be divided into figurative and abstract forms, conveying people’s spiritual beliefs and ideological concepts. The color schemes are bright and harmonious, integrating cultural, artistic, and practical values. Their cultural connotations include Dragon Boat Festival customs for warding off evil spirits, expressions of affection, fertility worship, and auspicious blessings. Conclusion: Northeast folk sachets reflect the distinctive lifestyle and folk customs of the region, embodying the spiritual pursuits of Northeastern people and serving as an important carrier of Northeastern folk culture. Research and preservation of these sachets contribute significantly to the inheritance and promotion of traditional Chinese culture.
Keywords: Art Artistic Feature; Sachet; Northeast China; Folk Culture